Higher Peak Fat Oxidation During Rowing vs. Cycling in Active Men and Women. Issue 1 (January 2021) - Astorino, Todd A.; Oriente, Chandler; Peterson, Jill; Alberto, Giannina; Castillo, Erica Elena; Vasquez-Soto, Ulices; Ibarra, Esmerelda; Guise, Victoria; Castaneda, Ivan; Marroquin, Joel R.; Dargis, Rachel; Thum, Jacob S.
Abstract : Abstract: Astorino, TA, Oriente, C, Peterson, J, Alberto, G, Castillo, EE, Vasquez-Soto, U, Ibarra, E, Guise, V, Castaneda, I, Marroquin, JR, Dargis, R, and Thum, JS. Higher peak fat oxidation during rowing vs. cycling in active men and women. J Strength Cond Res 35(1): 9–15, 2021—This study compared fat and carbohydrate oxidation (CHOOx) between progressive rowing and cycling. Initially, 22 active healthy adults (age = 27 ± 8 years) performed incremental cycling and rowing to volitional fatigue to assess maximal oxygen uptake (V[Combining Dot Above]O2 max) and maximal heart rate (HRmax). The order of 2 subsequent sessions was randomized, performed 2 hours postmeal, and included a warm-up followed by three 8-minute stages of rowing or cycling at 60–65, 70–75, and 80–85 %HRmax. During exercise, power output was modified to maintain work rate in the desired range. Gas exchange data and blood samples were obtained to measure fat and CHOOx and blood lactate concentration. Fat oxidation (FOx) increased during exercise ( p < 0.001) and there was a main effect of mode ( p = 0.03) but no modeXintensity interaction ( p = 0.33). Peak FOx was higher in response to rowing vs. cycling (0.23 ± 0.09 g·min −1 vs. 0.18 ± 0.07 g·min −1, p = 0.01). Carbohydrate oxidation increased during exercise ( p < 0.001) but there was no effect of mode ( p = 0.25) or modeXintensity interaction ( p = 0.08). Blood lactate concentration was lower ( p = 0.007) at the end of rowing vs. cycling (3.1 ± 1.0 mM vs. 3.9 ± 1.6 mM, d = 1.1). Prolonged rowing having equivalent calorie expenditure and intensity vs. cycling elicits higher peak FOx, which is likely attributed to greater muscle mass used during rowing.